Katholische Konfessionalisierung in Paderborn? Religiöse Prozesse in der Frühen Neuzeit

Max Schulze vs. Joana Dahlhoff - Schulze, Max (Joana Dahlhoff: Recherche patiente)

Shared Leadership: Neue Studien für die Unternehmenspraxis - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

HR-Manager als Intrapreneure - Wach, Bernhard; Krebs, Benjamin; Kabst, Rüdiger (HR-Trends 2021)

Contrastive Predictive Coding Supported Factorized Variational Autoencoder for Unsupervised Learning of Disentangled Speech Representations - Ebbers, Janek; Kuhlmann, Michael; Cord-Landwehr, Tobias; Haeb-Umbach, Reinhold (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
In this work we address disentanglement of style and content in speech signals. We propose a fully convolutional variational autoencoder employing two encoders: a content encoder and a style encoder. To foster disentanglement, we propose adversarial contrastive predictive coding. This new disentanglement method does neither need parallel data nor any supervision. We show that the proposed technique is capable of separating speaker and content traits into the two different representations and show competitive speaker-content disentanglement performance compared to other unsupervised approaches. We further demonstrate an increased robustness of the content representation against a train-test mismatch compared to spectral features, when used for phone recognition.

A Large-Scale Interview Study on Information Security in and Attacks against Small and Medium-sized Enterprises - Huaman, Nicolas; von Skarczinski, Bennet; Stransky, Christian; Wermke, Dominik; Acar, Yasemin; Dreißigacker, Arne; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Why Eve and Mallory Still Love Android: Revisiting TLS (In)Security in Android Applications - Oltrogge, Marten; Huaman, Nicolas; Amft, Sabrina; Acar, Yasemin; Backes, Michael; Fahl, Sascha (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Passivität als Widerstand gegen die Macht der Verhältnisse? Melvilles Bartleby, the scrivener aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute)

Happy clappy heile Welt? Wie angesichts von Krisen und Katastrophen eine schöne Welt besungen werden kann - Neumann, Anna (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

This is my Fight Song - Neumann, Anna; Katharina, Kammeyer; Vera, Uppenkamp (Musk als Lebensmittel)

Keller, Raabe, Fontane: ›nichts für den Durchschnittsleser‹. Miszellane Lektüren, ›imaginäre Leser‹ und Kanonisierungsprozesse in der Literaturkritik der zeitgenössischen Presse - Gretz, Daniela (Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert)

Miszellanes Lesen. Interferenzen zwischen medialen Formaten, Romanstrukturen und Lektürepraktiken im 19. Jahrhundert

Mit Aufgaben im inklusiven Mathematikunterricht professionell umgehen - Erkenntnisse einer Interviewstudie mit Lehrpersonen der Sekundarstufe - Häsel-Weide, Uta; Seitz, Simone; Wallner, Melina; Wilke, Yannik; Heckmann, Lara (QfI - Qualifizierung für Inklusion. Online-Zeitschrift zur Forschung über Aus-, Fort- und Weiterbildung pädagogischer Fachkräfte)

Conceptualiziation processes of 6th graders for rotational symmetry - Hattermann, Mathias; Häsel-Weide, Uta; Wallner, Melina (Proceedings of the 44th Conference of the International Group for the Psychology of Mathematics Education)

Zusammenhang zwischen familiären Lebenssituationen und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter. - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)

Bifurcation preserving discretisations of optimal control problems - Offen, Christian; Ober-Blöbaum, Sina
The first order optimality conditions of optimal control problems (OCPs) can be regarded as boundary value problems for Hamiltonian systems. Variational or symplectic discretisation methods are classically known for their excellent long term behaviour. As boundary value problems are posed on intervals of fixed, moderate length, it is not immediately clear whether methods can profit from structure preservation in this context. When parameters are present, solutions can undergo bifurcations, for instance, two solutions can merge and annihilate one another as parameters are varied. We will show that generic bifurcations of an OCP are preserved under discretisation when the OCP is either directly discretised to a discrete OCP (direct method) or translated into a Hamiltonian boundary value problem using first order necessary conditions of optimality which is then solved using a symplectic integrator (indirect method). Moreover, certain bifurcations break when a non-symplectic scheme is used. The general phenomenon is illustrated on the example of a cut locus of an ellipsoid.
Keywords: optimal control; catastrophe theory; bifurcations; variational methods; symplectic integrators

Learning ODE Models with Qualitative Structure Using Gaussian Processes - Ridderbusch, Steffen; Offen, Christian; Ober-Blöbaum, Sina; Goulart, Paul (2021 60th IEEE Conference on Decision and Control (CDC))

Multi-objective minimum time optimal control for low-thrust trajectory design - Vertovec, Nikolaus; Ober-Blöbaum, Sina; Margellos, Kostas
We propose a reachability approach for infinite and finite horizon multi-objective optimization problems for low-thrust spacecraft trajectory design. The main advantage of the proposed method is that the Pareto front can be efficiently constructed from the zero level set of the solution to a Hamilton-Jacobi-Bellman equation. We demonstrate the proposed method by applying it to a low-thrust spacecraft trajectory design problem. By deriving the analytic expression for the Hamiltonian and the optimal control policy, we are able to efficiently compute the backward reachable set and reconstruct the optimal trajectories. Furthermore, we show that any reconstructed trajectory will be guaranteed to be weakly Pareto optimal. The proposed method can be used as a benchmark for future research of applying reachability analysis to low-thrust spacecraft trajectory design.

Fractional Damping Through Restricted Calculus of Variations - Jiménez, F.; Ober-Blöbaum, Sina (Nichtlineare Sci 31)

Der steinige Weg vom Wissen zum Können: Zum schwierigen Verhältnis von Theorie und Praxis bei der Betreuung zukünftiger Geschichtslehrkräfte in Langzeitpraktika - Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Theorie und Praxis in der Lehrerbildung.Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

„Da öffnet er ihnen das Verständnis, sodass sie die Schriften verstanden“ (Lk 24,45) - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)

The Rise of Interactional Multimodality in Human-Computer Interaction - Klowait, Nils; Ерофеева, Мария Александровна (The monitoring of public opinion economic&social changes)
The field of human-computer interaction (HCI) investigates the intersection between the design of devices and users. From an early focus on interaction modeling based on psychological experiments, the field has since experienced a shift towards the study of how actual humans interact with autonomous devices. The field became conductive to ethnographic, observational and videographic studies of human-device interaction. Conversation-analytic HCI became possible. That said, this new wave of researchers was never truly able to dethrone the psychological common sense of the field. With recent developments in both the technical-sensorial capabilities and outward actuational range of embodied virtual agents, the field of HCI has once again returned to the question of the sequential unfolding of the interaction between users and intelligent agents, and the multimodal interactional repertoire that is deployed throughout. This review will highlight the situational orientation of high-impact research in the field, and relate it to the cotemporaneous development of ethnomethodological and conversation analytic frameworks. Acknowledgments. The article was prepared in the framework of a research grant funded by the Ministry of Science and Higher Education of the Russian Federation (grant ID: 075-15-2020-908). The article was prepared in cooperation with the Sber (ex. – Sberbank’s) Gamification Lab.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

Home-Office. Kulturelle Formationen häuslicher Arbeit - Miggelbrink, Monique; Bartz, Christina (Selbstbehältnisse. Orte und Gegenstände der Aufbewahrung von Subjektivität)

Forschungsfelder für Künstliche Intelligenz in der strategischen Produktplanung - Ködding, Patrick; Dumitrescu, Roman (Digitalisisierung souverän gestalten)

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (AIP Advances)

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter (Angewandte Chemie International Edition)
Exceptionally electron-rich, nearly trigonal-planar tricyanidometalate anions [Fe(CN)3]7− and [Ru(CN)3]7− were stabilized in LiSr3[Fe(CN)3] and AE3.5[M(CN)3] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid-state route, single crystals from alkali metal flux. While LiSr3[Fe(CN)3] crystallizes in P63/m, the polar space group P63 with three-fold cell volume for AE3.5[M(CN)3] is confirmed by second harmonic generation. X-ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm−1) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π-bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe−IV(CN−)3]7−, quantum chemical calculations reveal non-innocent intermediate-valent CN1.67− ligands and a closed-shell d10 configuration for Fe, that is, Fe2−.
Keywords: General Chemistry; Catalysis

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Quantifying the refractive index of ferroelectric domain walls in periodically poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optics Express)
Domain walls (DWs) in ferroelectric (FE) and multiferroic materials possess an ever-growing potential as integrated functional elements, for instance in optoelectronic nanodevices. Mandatory, however, is the profound knowledge of the local-scale electronic and optical properties, especially at DWs that are still incompletely characterized to date. Here, we quantify the refractive index of individual FE DWs in periodically-poled LiNbO 3 (PPLN) single crystals. When applying polarization-sensitive optical coherence tomography (PS-OCT) at 1300 nm using circular light polarization, we are able to probe the relevant electro-optical properties close to and at the DWs, including also their ordinary and extraordinary contributions. When comparing to numerical calculations, we conclude that the DW signals recorded for ordinary and extraordinary polarization stem from an increased refractive index of at least Δn > 2·10 −3 that originates from a tiny region of < 30 nm in width. PS-OCT hence provides an extremely valuable tool to decipher and quantify subtle changes of refractive index profiles for both inorganic and biomedical nanomaterial systems.
Keywords: Atomic and Molecular Physics; and Optics

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing. - Budde, Kirsten; Barela, José A; Figueiredo, Gabriella A; Weigelt, Matthias (TeaP 2021 - Abstracts of the 63rd Conference of Experimental Psychologists.)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Abstract In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on “Data and data detectives with CODAP” in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.
Keywords: Education; Statistics and Probability

Integration fachwissenschaftlicher und fachdidaktischer Komponenten in der Lehramtsausbildung Mathematik Grundschule am Beispiel einer Veranstaltung zur Leitidee „Daten, Häufigkeit und Wahrscheinlichkeit“ - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya

When differential privacy meets NLP: The devil is in the detail - Habernal, Ivan (Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing)

Alternating Asymmetrical Phase-Shift Modulation for Full-Bridge Converters with Balanced Switching Losses to Reduce Thermal Imbalances - Rehlaender, Philipp; Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
Phase-shift modulated full bridge converters suffer from thermal imbalances of the inverter switches. The lagging leg switches are subject to larger commutation currents compared to those of the leading leg as the transformer current reduces in the freewheeling interval. Furthermore, after this interval, the energy in the series inductance may not be large enough to achieve zero-voltage switching (ZVS) for the leading leg. Both effects result in thermal imbalances. This paper analyzes the alternating-asymmetrical phase-shift modulation to achieve balanced conduction and switching losses for all four switches while showing that this modulation is easily implemented on standard DSPs. The modulation has been implemented to LLC converters where experimental measurement results proved its effectiveness for LLC converters by reducing the temperature deviation from 6.3 K to only 0.2 K such that the peak temperature is reduced from 95 °C to 92 °C. The paper also proves that the modulation can be utilized to improve the efficiency of LLC converters operated at very low gains while simultaneously reducing the junction temperature of all four switches compared to the conventional complementary modulation. Finally, EMI implications are analyzed, which show that the modulation may be beneficial for reducing the common-mode emissions around the operating frequency.
Keywords: Phase-Shifted Full Bridge; Full-Bridge Converter; Phase-Shift Control; Phase-Shift Modulation; LLC Converter; Thermal Balancing

Geometrisches Begriffsverständnis in der Grundschule am Beispiel der Begriffe Viereck, Rechteck und Quadrat - Bruns, Julia; Unterhauser, Elisabeth; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Zu den ersten geometrischen Begriffen, die Kinder bereits im Elementar- und Primarbereich lernen, zählen u. a. Viereck, Rechteck und Quadrat. Studien zeigen, dass Lernende bereits früh individuelle Vorstellungen, sog. individuelle Begriffskonzepte, zu diesen Begriffen aufbauen. Zwar wird die Entwicklung von Begriffsverständnis in verschiedenen mathematikdidaktischen Stufenmodellen dargestellt, diese sind jedoch generisch und beschreiben nicht explizit die Entwicklung der ersten individuellen Begriffskonzepte von Lernenden zu Viereck, Rechteck und Quadrat. Aus empirischer Sicht liegen verschiedene Studien vor, die einzelne Aspekte der individuellen Begriffskonzepte von Lernenden unterschiedlicher Altersgruppen zu diesen Begriffen ausleuchten. Um Begriffsbildungsprozesse aus empirischer Sicht detaillierter entlang der jeweils vorherrschenden individuellen Begriffskonzepte zu beschreiben, fehlen insbesondere Studien in der Grundschule, die alle vier Klassenstufen betrachten und dabei differenzierte Erkenntnisse zu verschiedenen theoretischen Indikatoren des Begriffsverständnisses liefern. Daher geht die vorliegende Studie der Frage nach, welches Verständnis der Begriffe Viereck, Rechteck und Quadrat Schülerinnen und Schüler der Jahrgangsstufen 1, 2, 3 und 4 zeigen. Dazu wurde eine Quasi-Längsschnittstudie mit N = 456 Grundschulkindern (ca. 100 pro Jahrgangsstufe) durchgeführt. Die Ergebnisse geben detaillierte Einblicke in die individuellen Begriffskonzepte der Lernenden und zeigen, dass Lernende zunehmend Eigenschaften der Figuren berücksichtigen, jedoch individuelle Begriffskonzepte über lange Zeit auch prototypisch geprägt sind. Implikationen dieser Ergebnisse für Forschung und Praxis werden diskutiert.
Keywords: Education; General Mathematics

Tocotronic - Hoffnung (2020). - Jacke, Christoph (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr.)

Teilhabe von Eltern an schulischem Lernen mit Family-Literacy-Programmen. Langzeiteffekte von „LIFE – Lesen in Familie erleben“ auf die elterliche Unterstützung beim Lesenlernen - Bonanati, Sabrina; Gruchel, Nicole; Kurock, Ricarda; Buhl, Heike M. (Die Deutsche Schule)
Family-Literacy-Programme stellen eine gute Möglichkeit dar, Eltern in Bildungsprozesse einzubeziehen. Am Beispiel des Programms „LIFE – Lesen in Familie erleben“ wird die Wirkung auf elterliche Unterstützung beim Lesenlernen von Erstklässler*innen unter Einbezug von Eltern- und Kinderperspektive untersucht. Sowohl direkt nach dem Programm als auch ein halbes Jahr später wirkte das Programm positiv auf verschiedene Arten der Anschlusskommunikation beim gemeinsamen Lesen.
Keywords: Kooperation; Familie; Lesekompetenz; Längsschnittstudie; Intervention

Schule und außerschulische Bildungspartner an der Schnittstelle von formalen und non-formalen Bildungsprozessen - Empirische Befunde zur Kooperation und professionellen Handlungskompetenz - Limpinsel, Inga; Engemann, Mario; Neuberger, Olga; Serova, Katja; Aßmann, Sandra (Kooperation - Koordination - Kollegialität. Befunde und Diskurse zum (multi-)professionellen Zusammenwirken pädagogischer Akteur*innen an Schulen)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, Mario; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Lehrerkooperation vor dem Hintergrund der Digitalisierung: Eine Untersuchung innerhalb von Fachkollegien im gymnasialen Schulfach Pädagogik - Engemann, Mario; Herzig, Bardo

When agency “fits” regardless of gender: Perceptions of applicant fit when job and organization signal male stereotypes - Dutz, Regina; Hubner-Benz, Sylvia; Peus, Claudia (Personnel Psychology)
Evaluators’ fit assessments are not only influenced by applicants’ qualities, but also by stereotypes, especially in recruitment for high‐status jobs in male‐dominated fields. The unidimensional agentic stereotype of these work contexts signals agentic job and organizational requirements (stereotypically male qualities such as achievement orientation), although the actual requirements usually also include communality (stereotypically female qualities such as interpersonal skills). In five experiments, we investigate the relevance of perceived applicant agency for perceived applicant fit, the influence of recruitment material, contextual differences, and the role of applicant gender. Our findings indicate that perceived applicant agency drives perceived person‐job and person‐organization fit in strictly male stereotyped work contexts, regardless of gender, and agentic recruitment material enhances this effect. Contrasting different contexts (high‐ with low‐status jobs and a male‐dominated with a gender‐balanced and female‐dominated field) revealed that the relevance of perceived agency increases with perceived job status, and the relevance of perceived communality decreases with the expected share of men. Although women were perceived as highly agentic in strictly male stereotyped work contexts, their need to be perceived as agentic also was higher than for men, due to the perceived lack of fit between women and high‐status jobs.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Narratives in entrepreneurial ecosystems: drivers of effectuation versus causation - Hubner-Benz, Sylvia; Most, Fabian; Wirtz, Jochen; Auer, Christine (Small Business Economics)
This paper introduces narratives in entrepreneurial ecosystems as drivers of effectuation vs. causation. Drawing on 43 interviews with successful players in Silicon Valley, Munich, and Singapore, we found ecosystem-specific narratives indicate what is common, appropriate, and successful in each ecosystem, and these narratives encourage either effectuation or causation. Our findings indicate that the narratives in the ecosystem in Silicon Valley facilitate effectuation, in Munich causation, and in Singapore a cautious balance of both. Our research suggests that narratives can explain mechanisms how ecosystems influence entrepreneurship: the national culture, market characteristics, available resources, and networks in an ecosystem spark ecosystem-specific narratives, which in turn shape tendencies towards effectuation and causation. Thereby, we introduce a new ecosystem-focused perspective on predictors of effectuation and causation.
Keywords: Economics and Econometrics; General Business; Management and Accounting

Weder - Noch. Was mich theologisch prägt - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. (https://www.theomag.de/129/hsw22.pdf))

Fehlerbearbeitung bei mathematischen Textaufgaben – Sprachliche und strategische Fehlerursachen und ihre Bearbeitung - Prediger, Susanne; Dröse, Jennifer (Lernen und Lernstörungen, 10(2))